Occurrence of Pediculus humanus capitis in Relation to their Personal Hygiene and Social Behaviour Among the Children in Dhaka City (Bangladesh Journal of Zoology, 2016)
Abstract not availableBangladesh J. Zool. 43(2): 327-332, 2015